Influence of nitrogen, phosphorus and potassium on growth parameters, leaf nutrient composition and yield of litchi (Litchi chinensis) - RAI, MATHURA; DEY, P; GANGOPADHYAY, K K; DAS, BIKASH; NATH, VISHAL; REDDY, N N; SINGH, H P (The Indian Journal of Agricultural Sciences, 2014)
A field expcriment Was conducted during 1995-2000 to study effect of N, P and K on growth parameters, leaf nutrient composition and yield or'China' litchi (Litchi chineinsis Sonn.). An application of N significantly influenced trce height, volume, trunk girth, spread, fruit length, fruits volume, TSS and ascorbie acid content. Application of phosphorus @ 220 g/year recorded the maximum vegetative growth and yield (31.02 kg/plant). Among the physio-chemical characteristics of the fruits, seed weight, pulp weight, TSS and acidity were significantly influenced by the application of phosphorus. The Application of potassium @ 249 g k/tree/yeay resulted in the maximum yield (27.62 kg/plant), tree height (3.52 m), spread (5.50 m) and tree volume (56.98 ml). Among the physico-chemical characteristics of litchi fruit, ascorbic acid content was signilicantly affected by potassium. Leaf nutrient Composition varied from 1.10 to 1.55% for N; 0.17 to 0.29% for P and 0.69 to [.28% for K. Quadratic relationship hold good between leaf nutrient compositions and yield of litchi. The respective equations involving leaf N, P and K contents described 75-80% variations in yield of litchi.